Acquisition of posture control through of high postures in extremely preterm infants with diagnoses of Bronchopulmonary Dysplasia severe: case report. - Martins, Tamiris Beppler; Silva, Camila Fadel da; Rafael, Aline Dandara; Martinello, Micheli; Jonhston, Cíntia; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: with the increased survival of immature newborns, the incidence of bronchopulmonary dysplasia is increasing, as well as a significant increase in the number of children with delayed neuropsychomotor development. Objective: To report the experiences in a physical therapy intervention program based on the neuroevolutives high positions in the development of cervical control and trunk, in a higk-risk young child diagnosed with bronchopulmonary dysplasia. Method: case report of a female child, chronological age of six months, corrected age of two and a half months, extremely premature very low birth weight, which held 28 sessions of physiotherapy. Results: after treatment, there was an increase of active movement; in the prone position was reached full cervical extension; the roll from supine to prone; in the sitting position remained good postural control; she remained in a standing position with cervical support and trunk requiring support at lower distal members. Conclusion: the high positions allowed greater interaction between child and the environment around herself, thus enabling a breakthrough in motor development for the acquisition of control cervical and trunk.